2022
DOI: 10.3390/nu14234980
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Food Vouchers and an Educational Intervention on Promoting Healthy Eating in Vulnerable Families: A Pilot Study

Abstract: Cost has been reported as the main barrier to healthy eating in vulnerable groups. We aimed to evaluate the effect of a nutrition education intervention on adherence to Mediterranean Diet and health when providing food vouchers. This pilot study has a randomized control trial design. We included 66 vulnerable users from the Red Cross of Zaragoza (Spain). Intervention and control group individuals received 120 euros/month of food vouchers over 3 months to be spent in supermarkets (60 euros/month if under 12 y) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a pilot study, Miguel-Berges et al [7] tested whether a 14-week unrestricted food voucher program with or without parallel nutrition education would lead to better food purchases. Vouchers could be used towards any food purchase, and the researchers received purchase data directly from the participating supermarkets to assess any changes in food purchase behavior.…”
Section: Study Resultsmentioning
confidence: 99%
“…In a pilot study, Miguel-Berges et al [7] tested whether a 14-week unrestricted food voucher program with or without parallel nutrition education would lead to better food purchases. Vouchers could be used towards any food purchase, and the researchers received purchase data directly from the participating supermarkets to assess any changes in food purchase behavior.…”
Section: Study Resultsmentioning
confidence: 99%
“…The addition of a food provision component to remove barriers associated with the perceived higher price and inconvenience of healthy foods is also likely to have improved retention. Previous studies have shown that financial support improves adherence to a MD when accompanied by an educational intervention (35). We provided participants with options to choose MD components that met their personal food preferences, rather than being prespecified by study design, as personalisation has shown to lead to sustained changes in dietary behaviour (36).…”
Section: Discussionmentioning
confidence: 99%